THE INFLUENCE OF TOURISM ATTRACTION, FACILITIES AND SERVICE QUALITY ON INTEREST IN REVISITING TO TOURISM TAMAN MINI INDONESIA INDAH, JAKARTA - Alawiyah, Nur Aisyah; Wulandari, Ririn (Jurnal Doktor Manajemen (JDM), 2024)
This research aims to analyze and determine the influence of tourist attractions, facilities and service quality on interest in returning to the Taman Mini Indonesia Indah area, Jakarta. The population in this study were visitors to Taman Mini Indonesia Indah who had visited 2 or more times. The sample used in this research was 240 respondents, calculated based on the Hair Formula. This research uses a quantitative descriptive approach. The sampling method in this research is NonProbability Sampling with the technique used is Purposive sampling. The data collection method in this research uses a survey method, with the research instrument being an online questionnaire via Google Form. The data analysis method used in this research is statistical analysis in the form of SEM-PLS (Partial Least Square) version 3.0. The results of this research show that the tourist attraction variable has a positive and significant effect on interest in returning to visit. The facility variable has a positive and significant effect on interest in returning to visit and the service quality variable has a positive and significant effect on interest in returning to visit.Keyword: Tourist Attration, Facilities, Service quality, Interest in Revisiting